2019
DOI: 10.1177/0748233719879611
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of cytotoxic and genotoxic endpoints following sub-chronic oral exposure to titanium dioxide nanoparticles

Abstract: Health hazards of titanium dioxide nanoparticles (TiO2-NPs) have raised severe concerns because of the paucity of information regarding the toxic effects among the population. In the present research, the in vitro and in vivo cytotoxic potential of TiO2-NPs were evaluated using flow cytometric techniques. Further, in vitro and in vivo genotoxic endpoints were estimated by means of comet, micronucleus (MN), and chromosomal aberration (CA) assays. In vitro analysis was performed at the concentration range of 10–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 56 publications
0
34
0
Order By: Relevance
“…Intestinal inflammation was often accompanied by alterations in gene expression and activity TNF-α, IFN-γ, IL-2, IL-8, IL-10, NF-kB, cytochrome p450 (CYP450), cyclooxygenase-2 (COX-2), Ki67, and T-helper cells 1 (Th-1) [15,86,88,90]. Some studies reported increased genotoxicity in the form of DNA damage, micronuclei, and dysplastic alterations of tissues including the distal colon and liver, while others did not [15,35,[90][91][92][93][94]. Markers indicating the progression of tumors (COX-2, Ki68, p65, TNF-α, α-catenin), alteration of tumor-related pathways mitogenactivated protein kinase (MAPK) and olfactory/G-protein-coupled receptor family (GPCR) have been measured [15,88,92,95].…”
Section: In Vivo Toxicity Of E171mentioning
confidence: 99%
“…Intestinal inflammation was often accompanied by alterations in gene expression and activity TNF-α, IFN-γ, IL-2, IL-8, IL-10, NF-kB, cytochrome p450 (CYP450), cyclooxygenase-2 (COX-2), Ki67, and T-helper cells 1 (Th-1) [15,86,88,90]. Some studies reported increased genotoxicity in the form of DNA damage, micronuclei, and dysplastic alterations of tissues including the distal colon and liver, while others did not [15,35,[90][91][92][93][94]. Markers indicating the progression of tumors (COX-2, Ki68, p65, TNF-α, α-catenin), alteration of tumor-related pathways mitogenactivated protein kinase (MAPK) and olfactory/G-protein-coupled receptor family (GPCR) have been measured [15,88,92,95].…”
Section: In Vivo Toxicity Of E171mentioning
confidence: 99%
“…In vivo studies in rodents exposed to TiO 2 reported toxic effects such as inflammation, impairment of biological barrier functions (intestinal, placental, blood-testis), as well as the promotion of cancer development [ 7 , 10 , 11 ]. Overall, repeated exposure to these particles exhibiting cytotoxic, genotoxic and immunotoxic effects is considered to be an important health issue [ 12 14 ]. For the general population, there is accumulating evidence that the main uptake route is ingestion, since TiO 2 is produced at high volumes as a food grade pigment (E171 in EU) incorporated in many foodstuffs as well as in toothpaste, medicines and food supplements.…”
Section: Introductionmentioning
confidence: 99%
“…31 Our results extended knowledge of the previous in vitro genotoxicity studies with the comet assays in other human cells where the toxicity of nano-TiO 2 was shown. 5 Apoptosis is recognized as a distinct mode of programmed cell death for the elimination of cells with irreparable genetic damage. On the same line, our results of increased DNA damage through Comet assay ( Figure 7) were verified by getting increased apoptosis levels in nano-TiO 2 -treated cells (Figure 8).…”
Section: Discussionmentioning
confidence: 99%
“…6 Owing to their mega-production and wide use, the safety and toxicity concerns have equally become important for nano-TiO 2 . They behave differently, in comparison to bulk-TiO 2 , due to their small size and large surface area that increase their reactivity and penetration into human system 5 . It has been shown through various in vitro and in vivo studies that nano-TiO 2 entered the bloodstream after gastrointestinal absorption and damaged the liver, spleen, kidney, lungs, brain, and reproductive organs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation